(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article examines some of the local history and artefacts found in Kinross. In the first section, the author attempts to trace the history of a set of keys that were believed to have been thrown into Loch Leven when Mary Queen of Scots was imprisoned in the castle there. He then moves on to the history of the culdee hermitage on St Serf’s Inch, its origins, some of the finds that were unearthed there, and the ruins that could be observed on the island in the nineteenth century. The author also discusses the manufacture of vellum and parchment in the village of Kinnesswood near Loch Leven and includes quotes from letters he received from the children of John Birrell, one such manufacturer. Meeting notes for 12 March, 1860 are appended.